2009
DOI: 10.1007/s11250-009-9497-2
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza in backyard poultry of the Mopti region, Mali

Abstract: This study reports the first evidence of circulation of avian influenza viruses (AIV) in domestic poultry in Mali. In the Mopti region, where AIV have already been isolated in migratory water birds, we sampled 223 backyard domestic birds potentially in contact with wild birds and found that 3.6% had tracheal or cloacal swabs positive by real-time reverse transcription PCR (rRT-PCR) for type A influenza viruses (IVA) and that 13.7% had sera positive by commercial ELISA test detecting antibodies against IVA. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…It could also be due to too low titres of the virus in faeces which makes it undetectable by RT-PCR. Similar findings of absence of AIV RNA in seropositive birds have been reported previously (Obon et al, 2009;Molia et al, 2010;Sabarinath et al, 2011;Wakawa et al, 2012). Likewise, the evidence of LPAIV in commercial poultry in this study suggests that the birds could serve as carriers shedding the virus into the environment when immunity against AI is no longer sufficient, thereby playing a crucial role in the epidemiology of the disease and posing a potential public health risk especially to occupationally exposed humans in the study area.…”
Section: Discussionsupporting
confidence: 89%
“…It could also be due to too low titres of the virus in faeces which makes it undetectable by RT-PCR. Similar findings of absence of AIV RNA in seropositive birds have been reported previously (Obon et al, 2009;Molia et al, 2010;Sabarinath et al, 2011;Wakawa et al, 2012). Likewise, the evidence of LPAIV in commercial poultry in this study suggests that the birds could serve as carriers shedding the virus into the environment when immunity against AI is no longer sufficient, thereby playing a crucial role in the epidemiology of the disease and posing a potential public health risk especially to occupationally exposed humans in the study area.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was unexpected, because ducks are associated with maintenance of influenza virus in domestic birds. In fact, many studies conducted in LBMs and farms reported a higher prevalence of influenza in ducks compared with other poultry species 7,15–17 . It is not clear why influenza A virus was not detected in ducks in the markets in Kenya, particularly in light of the fact that the ducks stayed for longer periods of time in the market and were housed in the market together with geese and turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…In our surveillance, in all avian species, influenza A virus was more commonly detected in oropharyngeal specimens than in cloacal specimens by rt RT‐PCR. In a study of AI in backyard poultry in Mali in 2007, 2·2% of tracheal swabs and 1·3% of cloacal swabs tested positive for influenza A by rt RT‐PCR 16 . Experimental studies in ducks showed that viruses replicated to higher levels in the trachea than in the cloaca of both inoculated and contact birds, suggesting that the digestive tract is not the main site of H5N1 influenza virus replication in ducks 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a large African duck known to perform extensive intra-African movements, including trans-equatorial migration [20], and it breeds during the rainy season in sub-Saharan Africa. The PTT was < 3% of the bird's body mass [19], and we used an attachment technique [18] similar to the one described by Miller et al . [38] which proved successful in North America for tracking northern pintail ( Anas acuta ) during migration.…”
Section: Methodsmentioning
confidence: 99%
“…Both comb ducks and chickens have been tested positive for avian influenza viruses during the dry season in 2008 [18,19]. We ran our analysis every 8 days for successive periods during the study (a total of 15 consecutive 8-day periods from February to July 2007).…”
Section: Introductionmentioning
confidence: 99%